Preparation and Antitumoral Activity of Au-Based Inorganic-Organometallic Nanocomposites - Dalmases, Mariona; Pinto, Andrea; Lippmann, Petra; Ott, Ingo; Rodríguez, Laura; Figuerola, Albert (Frontiers in Chemistry, 2019)
The synergy between gelator molecules and nanostructured materials is currently a novel matter of study. The possibility to carefully design the skeleton of the molecular entity as well as the nanostructure's morphological and chemical features offers the possibility to prepare a huge variety of nanocomposites with properties potentially different than just the sum of those of the individual building blocks. Here we describe the synthesis and characterization of nanocomposites made by the unconventional combination of phosphine-Au(I)-alkynyl-based organometallic gelating molecules and plasmonic Au nanoparticles. Our results indicate that the interaction between the two moieties leads to a significant degree of aggregation in both hydrophilic and hydrophobic media, either when using DAPTA or PTA-based organometallic molecules, with the formation of a sponge-like hybrid powder upon solvent evaporation. The biological activity of the nanocomposites was assessed, suggesting the existence of a synergetic effect evidenced by the higher cytotoxicity of the hybrid systems with respect to that of any of their isolated counterparts. These results represent a preliminary proof-of-concept for the exploitation of these novel nanocomposites in the biomedical field.